2003
DOI: 10.1016/s0014-5793(03)00308-9
|View full text |Cite
|
Sign up to set email alerts
|

Disulfide pairings and secondary structure of porcine β‐microseminoprotein

Abstract: A sperm motility inhibitor isolated from porcine seminal plasma is identical to porcine L L-microseminoprotein (MSP). Circular dichroism (CD) and nuclear magnetic resonance (NMR) data showed that the native and recombinant porcine MSPs exhibit very similar structure. The ¢ve disul¢de pairings on porcine MSP were unambiguously assigned based on NMR data and further con¢rmed using structural calculations. Surprisingly, our derived pairings di¡er from those recently reported for ostrich MSP based on matrix-assist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…3. Although the disulfide bridges in SSPs were estimated from the data of porcine PSP94 (Wang et al, 2003), two S-S bonds, between Cys 22 and Cys 47 and between Cys 69 and Cys 92 , were determined by enzymatic digestion of intact SSP-1 (data not shown).…”
Section: Comparison Of the Amino Acid Sequences Of Psp94 Family Proteinsmentioning
confidence: 99%
“…3. Although the disulfide bridges in SSPs were estimated from the data of porcine PSP94 (Wang et al, 2003), two S-S bonds, between Cys 22 and Cys 47 and between Cys 69 and Cys 92 , were determined by enzymatic digestion of intact SSP-1 (data not shown).…”
Section: Comparison Of the Amino Acid Sequences Of Psp94 Family Proteinsmentioning
confidence: 99%
“…All resonance assignments, including backbone and side-chain atoms, the cis/trans conformations of proline residues, and disulfide-bridge pairings, have been previously completely defined. 10 A consensus chemical shift index (CSI) 15 generated using the 1 H a , 13 C a , 13 Cb, and 13 C 0 chemical shifts revealed that the secondary structure was primarily composed of nine b-strands and no a-helical structure (see Figure S1 in Supplementary Material). The existence of b-sheets was also detected based on crossover b-strand nuclear Overhauser enhancements (NOEs) of d aa (i,j) in the 13 C NOE spectroscopy (NOESY) data.…”
Section: Resonance Assignment and Structure Determination By Nmrmentioning
confidence: 99%
“…In our previous study on porcine MSP, in addition to showing that the secondary structure is composed mainly of b-strands, we found that the disulfide pairings of porcine MSP were different from those in ostrich MSP. 10 In the present study, we determined the tertiary structure of porcine MSP that is composed of two domains, an N-terminal domain composed of one double-stranded and one fourstranded antiparallel b-sheet, and a C-terminal domain composed of two double-stranded antiparallel b-sheets. A search using DALI, 11 CATH 12 and CE 13 found no significant structural similarity in the Protein Data Bank, further demonstrating the novel protein fold of porcine MSP.…”
mentioning
confidence: 99%
“…In the final CNS calculations we used ca 1000 NOE restraints, 59 φ-angle restraints based on 3 J HN-H α coupling constants and 20 hydrogen bonds. We also used the S-S bond arrangement (2-47, 15-39, 34-70, 37-46 and 61-84) reported for pMSP by Wang et al 29 Our structures deviate in one obvious way from the structure of Figure 1. The amino acid sequences of mature MSP from human (Hsap), pig (Sscr), rhesus monkey (Mmul), baboon (Pham), rat (Rnor), mouse (Mmus), chicken (Ggal), and ostrich (Scam).…”
Section: Structure Calculationmentioning
confidence: 99%
“…This arrangement is consistent with the disulfide pattern previously reported for pMSP. 29 A second round of structure calculations in CYANA, where the NOE cross-peak lists, shift assignment lists, dihedral angle constraints, hydrogen bond constraints, and the disulfide bond arrangement were used, resulted in an ensemble of structures with an RMSD to the mean structure of 0.9(±0.2) Å for both proteins for the backbone atoms in the structured parts of the protein (residues 2-8, 18-93 for hMSP and residues 2-8, 14-90 for pMSP) for the ten models with the lowest target function values. The calculated structures emerging from these calculations showed that the two MSP proteins are, as expected, very similar and consist of two domains connected by a three amino acid residue linker.…”
Section: Structure Calculationmentioning
confidence: 99%